2015
DOI: 10.1177/1708538115585261
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroarterial fistula: A review of the literature

Abstract: Ureteroarterial fistulas are rare, erosive defects that occur between the distal segments of the ureter and the adjacent blood vessels in individuals with urologic and vascular comorbidities. Characterized by diffuse, pulsatile bleeding into the urinary tract, this condition carries a significant mortality rate in the absence of early recognition. Recent treatment efforts have focused on use of endovascular stenting techniques as an alternative to open surgical closure of the underlying defects in hemodynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 14 publications
0
49
0
8
Order By: Relevance
“…However, the reported diagnostic rates with CT are only 42-50% in cases without aneurysms, because it is often difficult to detect a direct fistulous communication between the artery and ureter via cross-sectional imaging (Van den Bergh et al 2009). The current review demonstrated that the angiography was the best modality for the diagnosis of UAF; however, the angiography could detect the bleeding in still only 72.4% (Das et al 2016). Contrast extravasation into the ureter might not occur when a ureteral stent or clots are at the site and tamponade the leak.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…However, the reported diagnostic rates with CT are only 42-50% in cases without aneurysms, because it is often difficult to detect a direct fistulous communication between the artery and ureter via cross-sectional imaging (Van den Bergh et al 2009). The current review demonstrated that the angiography was the best modality for the diagnosis of UAF; however, the angiography could detect the bleeding in still only 72.4% (Das et al 2016). Contrast extravasation into the ureter might not occur when a ureteral stent or clots are at the site and tamponade the leak.…”
Section: Discussionmentioning
confidence: 79%
“…UAF is a rare complex problem involving multiple organ systems, usually occurring in patients with significant comorbid conditions due to malignancy, irradiation, previous surgical interventions and indwelling ureteral stents (Das et al 2016;Turo et al 2018). A previous report demonstrated that a pseudoaneurysm was detected in up to 38% of cases with UAF, and CT could show an enhancing mass near the crossing of the ureter (Van den Bergh et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding treatments AUF requires multidisciplinary approach. Currently endovascular therapy is preferred to open surgery given the frequency of complicated anatomic presentation in most patients secondary to previous comorbidity [6]. …”
Section: Discussionmentioning
confidence: 99%